The fairer, the more attractive? : tradeoffs, and understanding the psychological contract for contingent employees : a study of online recruitment tactics by prospective employers : a thesis submitted in the fulfillment of the requirements for the degree of Masters of Arts in Industrial Organisational Psychology, Massey University - Siu, Ellie So Man (Massey University, 2019)
This study examines how an employer’s Facebook reputation could impact on a jobseekers’ feeling of attraction, and thereby potential commitment to them. Employees may be more attracted to their work when they can rely on fair rewards and envision their goals with job stability. A total of N=114 final year students studying a psychology related degree participated in a simulated job seeking experience. In a 2 x 4 experimental design, (a) perceived justice and (b) permanency of job were manipulated in an online advertisement to assess their impact on (i) organisational attractiveness and (ii) potential commitment with equity sensitivity controlled. Affective commitment was found to be marginally significantly influenced by the interaction of (a) justice and (b) job security after controlling for significant benevolence and gender effect. Despite permanency of job not attaining statistical significance with any of the dependent variables, permanent positions seem to be more attractive and yield higher consistent mean scores across the commitment variables. An attractive job, or a fair organisation might only invoke feeling of strong emotional attachment when job security is promised. There appears to be an ambivalence cost for when there are fair processes and justice in employment but it is only a temporary placement. The value of this study is in the unique holistic view of understanding how job permanency and justice portrayed in the image of the organisation online together, prior to any interaction with job candidates can impact on the prospective commitment of job candidates in online recruitment. Practical implications for recruiting organisations might be to explicitly advertise the culture of fairness and specific fair rewards from high performance when advertising for Permanent and Temporary roles respectively (i.e. performance-based rewards and the opportunity to progress into permanent roles).
Keywords: Employees; Recruiting; Psychological aspects; Social media; Corporate image; Employee rights; Job security; College students; Attitudes; 520104 Industrial and organisational psychology (incl. human factors)